2021
DOI: 10.1021/acsnano.1c00647
|View full text |Cite
|
Sign up to set email alerts
|

Super-Hydrophilic Hierarchical Ni-Foam-Graphene-Carbon Nanotubes-Ni2P–CuP2 Nano-Architecture as Efficient Electrocatalyst for Overall Water Splitting

Abstract: Water splitting via an electrochemical process to generate hydrogen is an economic and green approach to resolve the looming energy and environmental crisis. The rational design of multicomponent materials with seamless interfaces having robust stability, facile scalability, and low-cost electrocatalysts is a grand challenge to produce hydrogen by water electrolysis. Herein, we report a superhydrophilic homogeneous bimetallic phosphide of Ni2P–CuP2 on Ni-foam-graphene-carbon nanotubes (CNTs) heterostructure us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
239
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(245 citation statements)
references
References 71 publications
6
239
0
Order By: Relevance
“…[ 4b,22 ] The existence of various defects can optimize and affect the adsorption free energy of the reaction intermediates. [ 11a ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4b,22 ] The existence of various defects can optimize and affect the adsorption free energy of the reaction intermediates. [ 11a ]…”
Section: Resultsmentioning
confidence: 99%
“…As we all know, a satisfactory electrocatalyst also needs to have a larger specific surface area, higher electron transfer rate and more active sites so the to achieve a more effective catalytic effect. [ 11 ] As a result, the design of bimetallic compounds for controllable modification and regulation of electronic structures to achieve the synergistic regulation of electrical conductivity and stability of electrocatalyst activity has gradually become a research hotspot. In addition, for transition metal base catalyst, the introduction of the second element in the host lattice can also make the electronic structure of the lattice obvious adjustment, so as to change the adsorption free energy of reaction intermediates and obtain good electrocatalytic property.…”
Section: Introductionmentioning
confidence: 99%
“…At 100 mA cm −2 , the Er 0.4 Fe-MOF/NF exhibited the lowest overpotential (248 mV), compared with bare NF (418 mV), precursor Fe-MOF/NF (336 mV) and commercial RuO 2 /NF (288 mV). It was notable that Er 0.4 Fe-MOF/NF exhibited excellent electrocatalytic activity, surpassing most of the previous OER catalysts [40][41][42][43][44][45][46][47][48][49], as shown in Figure 3b and Table S3. Er 0.4 Fe-MOF/NF needed an overpotential of 210 mV at low current density (10 mA cm −2 ) by the back sweep test (Figure S5).…”
Section: Electrochemical Properties Of Er 04 Fe-mof/nf Electrode Active Materialsmentioning
confidence: 86%
“…To expose more accessible active sites, various nanostructured TMPs have been designed and fabricated, including nanowires, nanospheres, nanotubes, and nanosheets [11][12][13][14]. Among various nanostructures, the three-dimensional (3D) opened nanoframes (NFs) are of particular interest, which achieve large surface area and high atomic utilization efficiency by hollowing out the interior embedded unfunctional atoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nanostructure engineering, the composition regulation, e.g., by rational design and synthesis of bimetallic phosphides, has also been recognized as an effective way to promote the catalytic activity [9]. Previous studies suggested that the redistribution of electrons can be induced by the strong interfacial interactions at the hybrid TMP heterointerface, leading to the improved electron conductivity and synergistic OER catalytic enhancement [9, 13,19]. For instance, Liang et al [20] reported that Ni 2 P-CoP heterointerfaces can create effective electron transport channels, leading to synergistically enhanced OER performance with a low overpotential of 320 mV to achieve a current density of 10 mA cm −2 in 1 mol L −1 KOH.…”
Section: Introductionmentioning
confidence: 99%